1973
DOI: 10.1128/aac.3.1.87
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bactericidal Effectiveness of Four Aminoglycoside Antibiotics

Abstract: The antibacterial activity of four aminoglycoside antibiotics (gentamicin, Sch 13706, tobramycin, and sisomicin) was tested against eight gram-negative and three gram-positive species. A total of 323 strains were studied by the broth dilution technique. Tobramycin and sisomicin had greater bacteriostatic and bactericidal activity against Pseudomonas strains than did gentamicin and Sch 13706. Of the four antibiotics, sisomicin was most active against Klebsiella, Enterobacter, Escherichia coli, indole-negative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
27
0
3

Year Published

1974
1974
1976
1976

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 8 publications
5
27
0
3
Order By: Relevance
“…Whether this reflects the presence in the hospital environment of a substantial number of gentamicin-resistant strains is difficult to assess. Nevertheless, the present in vitro studies have confirmed previous investigations (4,6,8), indicating that resistance to gentamicin among gram-negative rods isolated in hospitals was more common than that to sisomicin and that cross-resistance between the two drugs does not always exist. Of course, this situation might change when sisomicin is used more frequently.…”
Section: Bacteriological Results Are Indicated Insupporting
confidence: 80%
See 2 more Smart Citations
“…Whether this reflects the presence in the hospital environment of a substantial number of gentamicin-resistant strains is difficult to assess. Nevertheless, the present in vitro studies have confirmed previous investigations (4,6,8), indicating that resistance to gentamicin among gram-negative rods isolated in hospitals was more common than that to sisomicin and that cross-resistance between the two drugs does not always exist. Of course, this situation might change when sisomicin is used more frequently.…”
Section: Bacteriological Results Are Indicated Insupporting
confidence: 80%
“…This antibiotic is produced substantially as a single component and resembles most closely gentamicin C,A, a component of the gentamicin complex. From in vitro data and from preliminary clinical studies (4,6,8), no major difference is to be expected between gentamicin and sisomicin; however, cross-resistance between gentamicin and sisomicin does not always exist, and no comparative study has yet been published from the clinical point of view.The present investigation was undertaken to compare the efficacy and the tolerance of gentamicin and sisomicin when used to eradicate bacteriuria in patients with underlying diseases of the urinary tract. An in vitro comparison of gentamicin and sisomicin performed on a large number of recently isolated microorganisms will be presented as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall spectrum of antimicrobial activity in vitro ofthe new aminoglycoside antibiotic sisomicin (10) is similar to that of gentamicin, although sisomicin has been reported to show somewhat greater activity against Pseudomonas aeruginosa, Klebsiella sp., and indole-positive Proteus (2, 4,6,9,11). In this study we compared the activity of sisomicin and gentamicin in mouse protection tests against six clinical gram-negative isolates, including one strain each of Klebsiella sp., Escherichia coli, Enterobacter aerogenes, Serratia marscens, Proteus mirabilis, and Pseudomonas aeruginosa.…”
mentioning
confidence: 99%
“…Tube dilution assays were done in MuellerHinton broth as previously described (9). Grid studies were performed so that double dilutions of cephalothin, and cefazolin were combined with double dilutions of gentamicin or tobramycin.…”
mentioning
confidence: 99%